Update and critical appraisal of combined timolol and carbonic anhydrase inhibitors and the effect on ocular blood flow in glaucoma patients - Adam M Moss (Dove Medical Press, 2010)
Adam M Moss, Alon Harris, Brent Siesky, Deepam Rusia, Kathleen M Williamson, Yochai ShoshaniDepartment of Ophthalmology, Indiana University School of Medicine, Indianapolis, Indiana, USAAbstract: Topical hypotensive therapy with both timolol and carbonic anhydrase inhibitors has been shown to be efficacious at reducing intraocular pressure. Many prospective studies have also suggested that carbonic anhydrase inhibitors augment ocular blood flow and vascular regulation independent of their hypotensive effects. Although consistent in their findings, these studies must be cautiously interpreted due to the limitations of study design and specific blood flow imaging modalities. The purpose of this review is to appraise and critically evaluate the current body of literature investigating the effects of combined treatment with topical carbonic anhydrase inhibitors and timolol in patients with glaucoma with respect to ocular blood flow, visual function, and optic nerve head structure.Keywords: ocular blood flow, carbonic anhydrase inhibitor, timolol, glaucoma, visual function, optic nerve head